2005
DOI: 10.1161/01.atv.0000183727.90611.4f
|View full text |Cite
|
Sign up to set email alerts
|

Value of High-Density Lipoprotein (HDL) Subpopulations in Predicting Recurrent Cardiovascular Events in the Veterans Affairs HDL Intervention Trial

Abstract: An altered HDL subpopulation profile marked with low alpha-1 and alpha-2 levels and a high alpha-3 level in coronary heart disease patients indicated an elevated risk for new CVD events. Moreover, alpha-1 and alpha-2 levels were superior to HDL-C levels in risk assessment in patients with low HDL-C in VA-HIT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
164
2
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 250 publications
(184 citation statements)
references
References 35 publications
9
164
2
8
Order By: Relevance
“…(37,38) Differences in distribution and size of HDL-P have been related to CVD risk. (39)(40)(41)(42)(43)(44)(45)(46) Whether there is a unique important protective effect of size of HDL-P measured by NMR spectroscopy requires better assessment of the characteristics and metabolism by size of HDL-P. (39) Large rather than small LDL-P were more strongly related to risk of CHD death for MRFIT men with MetSyn, especially among men without morbid CV events in the first 6 years of the trial. Recent reports from the MESA (36) and the VA-HIT trial (35) have shown that markers of LDL-P rather than size may be a more important determinant of the risk of CHD.…”
Section: Discussionmentioning
confidence: 99%
“…(37,38) Differences in distribution and size of HDL-P have been related to CVD risk. (39)(40)(41)(42)(43)(44)(45)(46) Whether there is a unique important protective effect of size of HDL-P measured by NMR spectroscopy requires better assessment of the characteristics and metabolism by size of HDL-P. (39) Large rather than small LDL-P were more strongly related to risk of CHD death for MRFIT men with MetSyn, especially among men without morbid CV events in the first 6 years of the trial. Recent reports from the MESA (36) and the VA-HIT trial (35) have shown that markers of LDL-P rather than size may be a more important determinant of the risk of CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of large HDL particles accompanied by high levels of small HDL particles predicted higher risk of cardiovascular disease events in a recent sub-analysis of the Veterans' Affairs HDL Intervention Trial [11]. HDL subclass distribution during fibrate treatment may thus be clinically interesting.…”
Section: Introductionmentioning
confidence: 99%
“…There is also increasing interest in treating other lipoprotein abnormalities in type 2 diabetes by reducing triacylglycerol [10,11] and/or raising HDL-cholesterol (HDL-C) [12,13]. Fibrate therapy can improve both of these, but there are concerns about combining them with statins because of adverse events [14] and the failure of the Fenofibrate Intervention and Event Lowering in Diabetes (FIELD) trial to demonstrate CVD-risk reduction with fenofibrate [15].…”
Section: Introductionmentioning
confidence: 99%